Femicide and forensic pathology: Proposal for a shared medico-legal methodology. (February 2023) - Cecchi, Rossana; Masotti, Vittoria; Sassani, Matilde; Sannella, Alessandra; Agugiaro, Giulia; Ikeda, Tomoya; Pressanto, Davide Maria; Caroppo, Emanuele; Schirripa, Maria Laura; Mazza, Marianna; Kondo, Toshikazu; De Lellis, Pietro
Highlights: Femicide is a murder due to the failure to recognize the victim's right to self-determination. There is a need for homogeneous methodology for the study of female homicides. Male and female homicides can be considered as two distinct victimological phenomena. Injuries and circumstantial patterns in femicides could represent evidence of a specific murder, deserving a specific regulatory framework. More studies with a standardized data collection are needed to corroborate the theory of this paper. Abstract: In a previous work, authors have proposed a medico-legal definition of femicide as the murder due to the failure to recognize the right of self-determination of women . The aim of this paper was to apply the proposed definition to a cohort of cases to characterise femicides and female homicides and assess whether femicides can be considered a distinct entity or not. A comparison between female and male homicides was performed to assess common and distinctive features. Femicides were identified and compared to the cohort of non-femicide female murder. Results were compared to those reported in published forensic studies. Significant associations between female and male homicides were found for sex and partner/ex-partner offender, sex and indoor homicide and sex and asphyxia as dynamic of death emerged. A higher prevalence of indoor homicides and asphyxiation and of partner relationships were documented in female homicides. Gunshot, blunt injuries and cut wounds are well represented in both types of homicides. Most affected sites are back and chest in male homicides, and head, breasts, pubis, and limbs in female homicides. When comparing femicides and female homicides, a positive association between strangulation as harmful mean and a negative one between femicides and indoor homicides were found. Male and female homicides can be considered as two distinct victimological phenomena. Focusing on femicide allows to establish injuries and circumstantial patterns, that could represent evidence of a specific murder. More studies with a standardized data collection are needed to corroborate the theory of this paper.